EFFECT OF PARTIAL REPLACEMENT OF SOME PLANT SOURCES IN QUALITY AND SENSORY CHARACTERISTICS OF PROCESSED OF GOOSE MEAT BURGER - & Al-Shamery, Zangana (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The aim of this experiment was to study the effect of replacing of some plant sources oat , wheat germ, rice and mushroom  with percent 10% for each instead of goose meat on chemical composition , physical , microbial and sensory characteristics of process burger . The results showed significant increase (p